Endocrine Therapy for the Functional Recovery of Spinal Cord Injury - Wang, Hui; Zhou, Wen-xian; Huang, Jin-feng; Zheng, Xuan-qi; Tian, Hai-jun; Wang, Bin; Fu, Wei-li; Wu, Ai-min (Frontiers in Neuroscience, 2020)
Spinal cord injury (SCI) is a major cause of physical disability and leads to patient dissatisfaction with their quality of life. Patients with SCI usually exhibit severe clinical symptoms, including sensory and motor dysfunction below the injured levels, paraplegia, quadriplegia and urinary retention, which can exacerbate the substantial medical and social burdens. The major pathological change observed in SCI is inflammatory reaction, which induces demyelination, axonal degeneration, and the apoptosis and necrosis of neurons. Traditional medical treatments are mainly focused on the recovery of motor function and prevention of complications. To date, numerous studies have been conducted to explore the cellular and molecular mechanism of SCI and have proposed lots of effective treatments, but the clinical applications are still limited due to the complex pathogenesis and poor prognosis after SCI. Endocrine hormones are kinds of molecules that are synthesized by specialized endocrine organs and can participate in the regulation of multiple physiological activities, and their protective effects on several disorders have been widely discussed. In addition, many studies have identified that endocrine hormones can promote nerve regeneration and functional recovery in individuals with central nervous system diseases. Therefore, studies investigating the clinical applications of endocrine hormones as treatments for SCI are necessary. In this review, we described the neuroprotective roles of several endocrine hormones in SCI; endocrine hormone administration reduces cell death and promotes functional repair after SCI. We also proposed novel therapies for SCI.